(untitled) (Research, Society and Development, 2022)
Diabetes mellitus is a metabolic syndrome of multiple origins resulting from a lack of insulin or the inability of insulin to adequately exert its effects. It is a disease characterized by permanently high blood sugar levels. This disease carries alterations in the metabolism, and as a consequence of this lack of control there can be oral health complications, such as gum and periodontal infections. The diagnosis of the degree of the disease is what governs the conduct of the dental professional. Thus, the objective of this work was to describe the importance of theoretical and practical knowledge in patients with Diabetes mellitus in dental treatments. To this end, an exploratory literature review was carried out regarding the role of the dental surgeon in the care of diabetic patients within the parameters of dentistry. For this, a bibliographic survey was carried out in the platforms Google Scholar, SciELO, and Capes journals. For the searches the following keywords were used: diabetes in dentistry, diabetes mellitus, oral diseases. As a result of the evaluation of the different works about the subject presented in the literature, it was observed that the pre-disposition of oral diseases related to diabetes is greater in patients who do not have control of the disease. Thus, it is important that the dental surgeon is part of the multidisciplinary team and that he/she knows the adequate dental conducts to guarantee the best treatment to the patient, being clear about the diagnosis, glycemic indexes, use of anesthetics and adequate medications.